Aerodynamic characteristics of a delta wing aircraft under ground effect - Shams Taleghani, Arash; Ghajar, Arsalan (Frontiers in Mechanical Engineering, 2024)
The main objective of this study is to investigate the impact of ground effects on the aerodynamic coefficients of a delta wing aircraft model. Since the flow on the delta wing exhibits vortical flow inherently, it is crucial to examine the influence of ground effects under these conditions. An experimental study was conducted to enhance understanding of the aerodynamic behavior of an aircraft model incorporating a delta wing-body-vertical tail. Experiments were conducted in a subsonic wind tunnel with a test section measuring 2.8 m × 2.2 m. Measurements were taken using a sting type balance to determine the aerodynamic forces and moments. All experimental tests were performed at a Reynolds number of 1.5 × 10 6 , with the specific aim of examining and identifying the influence of the ground on aerodynamic coefficients. To investigate how ground effect affects the aerodynamic performance of the model, a fixed plate with an adjustable height was placed underneath it. The distance between the model and the ground was varied, and resulting data indicated that increased proximity to the ground improved longitudinal static stability. The results revealed that the presence of the ground plane resulted in a 6% increase in the maximum lift coefficient. Meanwhile, the lift increases around 25% due to ground effects at an angle of attack of 14° as it approaches the ground.The lift coefficient was enhanced across all angles of attack, while the induced drag coefficient decreased, resulting in an overall increase in aerodynamic efficiency. The lift curve slope saw a 16.9% increase when the model's height from the ground plane was less than half of the wing span. As the height decreased further, the aerodynamic center shifted backward, leading to an increase in longitudinal static stability. The rolling moment and yawing moment coefficients becomes unstable at angles of attack above 30°.